Suspiciously timed trade disputes - Paola Conconi; David R. DeRemer; Georg Kirchsteiger; Lorenzo Trimarchi; Maurizio Zanardi (Hungarian Academy of Sciences, Institute of Economics, 2015)
This paper shows that electoral incentives affect the occurrence of trade disputes. Focusing on WTO disputes filed by the United States during the 1995-2012 period, we show that U.S. presidents are more likely to initiate a dispute in the year preceding their re-election date. Moreover, disputes filed by the U.S. tend to target industries that are important to swing states in the presidential election. To explain these regularities, we develop a theoretical model in which an incumbent can file a trade dispute to appeal to voters motivated by reciprocity. The incumbent's ability to initiate a dispute during the re-election campaign provides an advantage over the challenger, who cannot commit to file the dispute if elected. If voters' ideological preferences are not too strong in favor of either candidate, the incumbent will file a trade dispute to increase his re-election chances.
Keywords: F13; D72; D78; D63; 330; trade disputes; elections; reciprocity